SketchUp - Fane, Bill; Harrison, Mark; Reilly, Josh (--For dummies., 2020)
"Whether you are totally new to 3D modeling or have already explored the world of 3D modeling, this is the SketchUp book that sets you up to conquer the basics and take your models to the next level. Start by practicing the fundamentals of design and then learn to think in 3D. Apply textures to make beautiful designs and use components to make smart, easy-to-present models. Draw quickly and accurately at the same time! Then apply your skills to home and interior design, woodworking and 3D printing, or any kind of project where you need to turn ideas into useful 3D plans."--Page 4 of cover.